PENINGKATAN PENGETAHUAN REMAJA MENGENAI PEMENUHAN GIZI SEIMBANG MELALUI ISI PIRINGKU DI MAN 1 SURAKARTA - Harisma Kusumawardani; Luluk Ria Rakhma; Nadia Aqiela Laili; Aliya Maharani Putri; Dwi Anggraini; Shofi Mela Rosida; Khantsa Mastura; Rara Rahma Fadilla; Chindi Astuti Anjellia Salsabila (Universitas Mataram, 2022)
Consumption of a balanced nutritional diet in adolescents can prevent various kinds of nutritional problems. Currently, many problems related to balanced nutrition are experienced by teenagers, which if not addressed immediately will have an impact until they are adults. Lack of knowledge in adolescents about fulfilling nutritional needs according to balanced nutrition will affect attitudes and behavior in eating wrong so that adolescent health problems arise. So teenagers need to be equipped with knowledge of how to fulfill balanced nutrition so that these health problems are resolved. To increase the knowledge of teenagers so that they can change their attitude to consume a balanced diet. By providing education and awareness of the importance of paying attention to food intake according to needs through